Stability Optimization Strategies of Cathode Materials for Aqueous Zinc Ion Batteries: A Mini Review - Gan, Yi; Wang, Cong; Li, Jingying; Zheng, Junjie; Wu, Ziang; Lv, Lin; Liang, Pei; Wan, Houzhao; Zhang, Jun; Wang, Hao (Frontiers in Chemistry, 2022)
Among the new energy storage devices, aqueous zinc ion batteries (AZIBs) have become the current research hot spot with significant advantages of low cost, high safety, and environmental protection. However, the cycle stability of cathode materials is unsatisfactory, which leads to great obstacles in the practical application of AZIBs. In recent years, a large number of studies have been carried out systematically and deeply around the optimization strategy of cathode material stability of AZIBs. In this review, the factors of cyclic stability attenuation of cathode materials and the strategies of optimizing the stability of cathode materials for AZIBs by vacancy, doping, object modification, and combination engineering were summarized. In addition, the mechanism and applicable material system of relevant optimization strategies were put forward, and finally, the future research direction was proposed in this article.